Dampak Optimalisasi Edukasi Untuk Peningkatan Peran Ibu dalam Mencegah Kekerasan Pada Anak Usia Sekolah - Rasmita, Dina; Setiawan; Dewi Elizadiani Suzza; Diah Arruum (Forum Kerjasama Pendidikan Tinggi, 2025)
Violence against children continues to increase in many parts of the world, including Indonesia. School-aged children are particularly vulnerable to violence. Mothers have an important role as the primary caregiver closest to the child and the first person who can detect changes in behavior or emotions in children and signs of child abuse. This service activity aims to increase the role of mothers in preventing violence in school-age children by increasing mothers' knowledge of violence prevention. The community service activity was carried out on 4 December 2024, involving 35 mothers with school-age children, who were given education, pre-test, and post-test questionnaires. The pre-test and post-test results showed an increase in knowledge related to violence prevention in education participants. Before the education was given, there were 11 people (31.4%) who had good knowledge about preventing violence in children. In comparison, after the education was given, there were 17 people (48.6%) who had good knowledge about preventing violence in children. Providing education can improve mothers' knowledge of preventing violence in school-age children. There is a need for continuous education on child abuse so that mothers can detect early signs of child abuse as an effort to prevent violence.